Designing an Attribute-Based Signature Scheme with Server-Aided Verification for Healthcare Monitoring in Metaverse - Shivani Goel; Mridul Kumar Gupta; Saru Kumari (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Introducing the metaverse into the context of attribute-based signatures (ABS), we explore a cryptographic landscape where digital identities transcend physical limitations. In this realm, ABS serves as the gateway for individuals or entities to sign digital artifacts based on predefined attributes, ensuring anonymity while meeting specific criteria. Within the metaverse, ABS schemes play a pivotal role in scenarios where privacy, access control, and fine-grained authorization are paramount, such as secure communication and digital authentication systems, including e-healthcare. However, the computational cost of signature verification remains a significant hurdle in existing ABS schemes. To address this challenge, we present an attribute-based signature scheme with server-aided verification for healthcare monitoring in metaverse. By leveraging server-aided verification criteria, we aim to enhance efficiency, reduce processing time, and optimize the practicality of ABS schemes within the dynamic landscape of the metaverse, particularly in the context of e-healthcare applications.